2019
DOI: 10.5897/jaerd2019.1074
|View full text |Cite
|
Sign up to set email alerts
|

Causes of losses and the economic loss estimates at post-harvest handling points along the beef value chain in Uganda

Abstract: Uganda's beef industry has been growing slowly and requires sustained monitoring of actors at postharvest handling points in order to decrease public health risks and losses. This study documented causes of losses and estimated economic values at post-harvest handling points along the beef value chain. It was carried out at slaughter houses, transporters and butcher shops in the districts of Western, Central and Eastern Uganda. A cross sectional study was conducted among meat handlers who were interviewed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…With the multiplier effect, (across multiple carcasses) these are substantial losses to stakeholders in this pork value chain. This is in agreement with a study by Juliet et al [77] in Uganda where drip loss was found to be the second major cause of beef losses, together with meat wastage (drops of meat and bones that fall off during cutting of beef for sale) where the two factors led to losses of up to 787.50 USD daily per district of study.…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…With the multiplier effect, (across multiple carcasses) these are substantial losses to stakeholders in this pork value chain. This is in agreement with a study by Juliet et al [77] in Uganda where drip loss was found to be the second major cause of beef losses, together with meat wastage (drops of meat and bones that fall off during cutting of beef for sale) where the two factors led to losses of up to 787.50 USD daily per district of study.…”
Section: Plos Onesupporting
confidence: 93%
“…Excessive exudates from meat have been associated with microbial spoilage [76]. Drip loss can also be a major source of food wastage and financial losses [77]. According to our study, the mean drip loss for the exudative categories of pork were 6.79% and 6.86% for PSE and RSE respectively in comparison to the 2.54% for optimal quality meat.…”
Section: Plos Onementioning
confidence: 63%
“…Health hazards through contamination of the meat during slaughter operations and from the surrounding, through uncontrolled release of waste and effluents are prevalent in the country" [11,12]. "Also, food contamination in the food supply chain as a result of improper handling cause food losses and foodborne illnesses that result in heavy economic losses" [13,14]. In Nigeria particularly in Kogi state, such economic losses have not been adequately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In one study in Uganda, the daily beef waste and drip loss was estimated in several butcheries and the sum of drip loss and beef waste gave the quantity loss per butchery. The daily quantity loss per butchery was higher for Mbale (3.19±2.60 kg) and lower for Mbarara (2.39±1.25 kg) and Kampala (2.39±1.61 kg) (14). This study aimed to determine meat preservation methods used by meat retailers and estimate the direct economic losses associated with meat spoilage in Nairobi, Kenya.…”
mentioning
confidence: 99%